Strategic management of administrative affairs in enhancing school administration services at smp it subulussalam lampung timur - Sasuman Tholib; Muhammad Zainal Abidin; Ahmad Ahadi (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to analyze administrative management strategies for improving school administrative services at SMP IT Subulussalam Lampung Timur. A qualitative approach with a descriptive method was employed. Data were collected through interviews, observations, documentation, and literature review. The findings reveal that the administrative management strategy encompasses structured planning, effective organization, professional implementation, and regular supervision and evaluation. Planning was based on the academic calendar and institutional needs, while tasks were distributed proportionally among administrative staff to support operational efficiency. Administrative services were delivered promptly, accurately, and courteously, enhancing stakeholder satisfaction. Regular evaluations conducted by the principal helped address emerging challenges and contributed to ongoing quality improvement. Issues such as limited human resources and infrastructure were mitigated through internal training and the utilization of available technology. The study implies that systematically developed administrative management strategies play a crucial role in enhancing the quality and sustainability of school administrative services.